Kesesuaian Pembangunan Rumah Susun Sederhana Sewa terhadap Standar Perumahan Ideal di Sukoharjo - Isandi Nurul Hasanah; Murtanti Jani Rahayu; Rufia Andisetyana Putri (Universitas Sebelas Maret Surakarta, 2017)
Construction of the rented simple flats is the option of government’s policy to meet the needs of adequate housing for low-income. The rented simple flats in Sukoharjo already inhabited 3 blocks of 6 blocks. The degree of occupancy will indirectly reflect quality the construction of flats. The problem in this study is whether development the rented simple flats in Sukoharjo complies with the standar of ideal housing. The purpose of research is the degree of conformity the rented simple flats in Sukoharjo as the standar of ideal housing. The method is used the deductive research methods with quantitative research. The analysis technique is used the analysis of scoring on any variable of the standards of ideal housing. The conclusions from this research is that there are nine variables known as the factors that influence the development of the rented simple flats in Sukoharjo as the ideal flats. The variables that have been suitable with the standar of ideal housing are the policy, the price of rent and accessibily. However, some variables that have not been optimal like the infrastructures, material contruction and the others. Consequently, Sukoharjo’s District Government and some of the parties concerned to repair deficiency and accommodate the needs of the community to achieve development the ideal flats. Keywords: Contruction of rented simple flats, standards of ideal housing, scoring analysis